Mudanya'da tarihsel araştırma ve mimari oluşumunun incelenmesi (2.Bölge) - Batum, Belde (My University, 1994)
Mudanya is one of the three towns which have shores Bursa existing in south Marmara Region. It has the history since 1400 B.C. It has a settlement of a narrow shore platform between the sea and back hills. It's also a working port between Bursa, its surroundings and Istanbul because of its position in the Gemlik Gulf. The town in times had been dominated by Bitinya, Pers, Roma and Bizans Empires. However the place got hold of by Turks after 1071 Victory of Malazgirt, Bizans got the control of it again during the crusodes. And it's added to Ottoman land during Orhan Bey period. Mudanya, for centuries, has been the first battle and guard place for the ones who wanted to get hold of Bursa from the seaside. In spite of the damaged pattern of the old settlement in the center Mudanya, it's mostly preserved. Until the XVII. century, the buildings were still standig but mostly damaged. The settlements were developed in east-west direction with a linear position, parallel to the sea shore. Mudanya, in which Turkish & Greek people lived together, is seen that Turkish dwellers prefered the inner parts of the city while the Greek prefered the sea shore for the sea trading. The buildings which form the pattern of the cities show the cultural, social, functional and aesthetic values of the living of the city dwellers. If there is the consciousness of the obligatory protection about these cities, this means that all these socio-cultural values are to be transferred to the next generations. With parallel these thought the buildings which form the historic pattern of the city XIare examined and new proposal are made for protection. During this research, firstly the physical properties of the city is examined then the historical development, the process of the physical development is explored. The analysis are made about the existing situation in the chosen zone. The forming of the buildings, the construction systems, the construction materials are explored and protecting proposals are decided. The in habitants in old buildings tried to repair them with respect to their possibilities but the lack of material support the buildings are lack of living confort.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1994
Keywords: Mudanya; 2.Bölge; Mimari oluşum